Applying the Problem-Based Learning (PBL) Method in Information and Communication Technology (ICT) Education - Raudatul Izmi (Jurnal Pendidikan Vokasi Indonesia, 2025)
Information and Communication Technology (ICT) learning is a process that involves the use of instructional media such as laptops, projectors, the internet, and other digital tools. This study aims to examine students' learning outcomes through the implementation of the Problem-Based Learning (PBL) model in ICT instruction. PBL emphasizes student engagement and critical thinking skills in solving assigned problems. Data collection techniques used in this study were observation and testing. The research subjects consisted of 18 ninth-grade students from SMP Swasta Darma Medan in the 2023/2024 academic year. The results showed that 13 students (72.22%) achieved mastery learning, while 5 students (27.77%) did not. These findings indicate that the application of the Problem-Based Learning model can enhance students' learning outcomes in ICT education.